A Survey of multi-biometrics and fusion levels - Taha, Khalaf Emad; Norrozila, Sulaiman (Informatics Publishing Limited, 2015)
The verification of the identities of individuals is becoming an increasingly important requirement in a variety of applications based on specific physiological or behavioral features. Most biometric systems that are currently in operation usually utilize a single biometric trait which called Uni-biometric systems. Other systems are called Mutli-biometrics systems which are utilize, or are capable of utilizing, more than one physiological or behavioral characteristic for enrolment either in verification or identification mode. It is generally believed that by integrating various biometric traits into one single unit, the limitations of uni-biomatic systems can be alleviated. Given that several biometric sources usually compensate for the weaknesses of single biometric fusion techniques has dealt primarily with the fusion at the score matching level.